METHODOLOGY FOR PREPARING PRESCHOOL CHILDREN FOR SCHOOL IN SHORT-TERM GROUPS - Ganiyeva Dildora Muqimovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
This article discusses the methodology for preparing preschool children for school in short-term groups. Based on the conclusions drawn, proposals were developed.